Megaesophagus - Ferreira Santos, Ruy (Cirugía del Uruguay, 1975)
he author presents his 30-year experience in the treatment of this condition. In 115 young patients, with grade I and II megaesophagi, without associated lesions or previous operative treatments, he performed a modified Ileller operation, via the abdominal route, with 80% good or excellent and lasting results. In slightly older patients, with long-lasting grade IV or III meg-esophagus or associated lesions, or in Beller failures, subtotaJ esophagectomy is performed, with esophagogastroplasty (up to 1955 -49 cases-via the anterior mediastinal route, in 2 times; since then -30 cases-by posterior mediastinal route, access by right thoracotomy, anastomosis by right cer \ 'icotomy, in a single stage). Good results, with low morbidity and mortality in the second variant. In the sequelae of Beller (reflux esophagitis and peptic stricture) or if an unusable mega-stomach is found, perform distal esophagectomy with jejunal interposition, with acceptable results, sometimes mild residual dysphagia.